The information society in an enlarged Europe - DUTTA, Soumitra (Institutional Knowledge at Singapore Management University, 2011)
Based upon detailed data collection and rigorous analysis, the book presents a benchmarking study of the 10 new member states and 3 candidate countries of the European Union as compared to the 15 incumbent countries with respect to the development of their information societies.